THU0230 HIF1A (RS11549465) and AKNA (RS10817595) gene polymorphisms are associated with primary sjÖgren's syndrome. (15th June 2017) - Hernandez-Molina, G; Rodríguez-Pérez, JM; Fernández-Torres, J; Lima, G; Pérez-Hernández, N; Lόpez-Reyes, A; Martínez-Nava, GA
Abstract : Background: HIF-1α is the main transcriptional regulator of cellular and developmental response to hypoxia, and also participates in the integration of the T cell receptor and cytokine receptor-mediated signals of CD4+ helper cells. Another transcription factor also involved in the immune responses is the AT-hook transcription factor (AKNA). Objectives: To evaluate the allele and genotype frequencies of polymorphic sites of HIF1A and ANKA genes in primary Sjögren's syndrome (pSS). Methods: We included 110 patients with pSS and 141 ethnically matched healthy controls. Three HIF1A gene polymorphisms (Pro582Ser, Ala588Thr, and C191T) and two AKNA genes polymorphism (-1372C > A, and Pro624Leu ) were genotyped using TaqMan probes in a Real-Time PCR instrument. Associations between pSS and genotypes, alleles and inheritance models of the SNPs of interest were evaluated by logistic regression adjusted by age and gender. Results: Most of the patients were females (95.4%), median age 55 years and median disease duration of 7.8 years. The C/T genotype and the T allele of the HIF1A Pro582Ser polymorphism protected against pSS (OR=0.22; 95% CI=0.09–0.52; P <0.01; and OR=0.26; 95% CI=0.12–0.58; P <0.01; respectively). Whereas under a recessive model adjusted by age and gender, the AKNA -1372C > A polymorphism A/A genotype was associated with an increased risk of pSS (OR=2.60; 95% CI=1.11–6.12; P =0.03). Parotid enlargement was associated with the HIF1A gene polymorphism (rs11549465), conferring protection for the C/T genotype vs. C/C (OR=0.22; 95% CI 0.05–0.90, P =0.03). The allele T of the same polymorphism was also associated with parotid enlargement (OR=0.24, 95% CI=0.65–0.95; P =0.04). We did not find any association with any other clinical or serological feature. Conclusions: We identified HIF1A Pro582Ser T allele and C/T genotype as well as AKNA -1372C > A polymorphism A/A genotype as genetic factors associated with pSS. Further studies in other populations are needed to validate our findings and to shed some light on their functional implications. References: Palazon A, Goldrath A, Nizet V, Johnson R. HIF transcription factors, inflammation and immunity. Immunity 2014; 41:518–28. Sims-Mourtada JC, Bruce S, McKeller MR, et al. The human AKNA gene expresses multiple transcripts and protein isoforms as a result of alternative promoter usage, splicing, and polyadenylation. DNA Cell Biol 2005;24:325–38. Disclosure of Interest: None declared